1983
DOI: 10.1037/0022-3514.44.4.817
|View full text |Cite
|
Sign up to set email alerts
|

More aggressive cartoons are funnier.

Abstract: Independent rankings of humor and aggressiveness were obtained for sets of cartoons drawn randomly from two different magazines. The correlation of median humor and median aggressiveness rankings ranged from .49 to .90 in six studies involving six different sets of cartoons and six different groups of subjects, including children and adults, high and low socioeconomic status (SES) individuals, and native- and foreign-born individuals. This correlation is consistent with Freudian, arousal, and superiority theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
2
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 4 publications
(5 reference statements)
1
23
2
1
Order By: Relevance
“…A state of hostility presumably leads to an appreciation of hostile humor. A number of behavioral studies are broadly consistent with these humor theories, which have suggested that more aggressive humor is funnier (e.g., McCauley et al, 1983). However, the behavioral evidence in favor of such theories is far from conclusive (Strickland, 1959; Byrne, 1961).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…A state of hostility presumably leads to an appreciation of hostile humor. A number of behavioral studies are broadly consistent with these humor theories, which have suggested that more aggressive humor is funnier (e.g., McCauley et al, 1983). However, the behavioral evidence in favor of such theories is far from conclusive (Strickland, 1959; Byrne, 1961).…”
Section: Discussionmentioning
confidence: 74%
“…There have been numerous theoretical links between humor and aggression in humor appreciation. Humor and aggression in humor appreciation have been most influential in social motivation theories, such as the psychoanalytic, superiority/disparagement, and arousal theories (McCauley et al, 1983). The Freudian theory of the joke was the first to propose aggression as a motivation of humor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most recent humour theories is the benign violation theory (McGraw & Warren, 2010), which claims that humour occurs only when a violation (of an expectation or a belief) occurs in a situation that is perceived to be benign and nonthreatening. Several studies examined the association between aggression/cruelty and humour, and found both a linear relationship (McCauley, Woods, Coolidge, & Kulick, 1983) and an inverted-U-shaped function (e.g., Herzog & Anderson, 2000). Research on more negative types of humour that induce amusement and aversion and studies that aimed at examining other mixed emotional states (e.g., combination of happiness and sadness) have been done in the past using cartoons (Samson & Meyer, 2010), music (Hunter, Schellenberg, & Schimmack, 2008) and film clips (Larsen & McGraw, 2011).…”
mentioning
confidence: 99%